(untitled) (Revista Argentina de Musicología, 2020)
In 1920, almost a year before the centennial celebrations of Independence, a particular situation in the cultural history of the Peruvian capital occurred. Two opera companies arrived one after the other, producing six uninterrupted months of opera. Alongside this event, the Teatro Forero was inaugurated and the national opera Ollanta was staged, after almost a year of Augusto Leguía’s second government known as “Patria nueva”. Even though both opera companies were successful, newspapers and magazines of the time instigated a rivalry between them that started before their arrival, and continued until the end of the second season. This article explores the reception of these two companies through the detailed readings of the theatre columns published in the magazines Hogar and Mundial to illustrate the place that opera occupied in the city, portraying their particularities within the political and cultural context of Lima in 1920, but also showing two modes of producing opera that extended all along Latin America during the beginning of the twentieth century.